Acceptance of the public address system as alternative media. - Dela Cruz, Jezrel Kirby T. (2011.)
This study entitled Acceptance of the Public Address system as Alternative Media uses the Shannon and Weaver Model of Communication, to asses the use of the PA system as an alternative medium of communication in Barangay Mat-y, Miag-ao, Iloilo., This study primarily aims to evaluate the residents' level of acceptance towards the PA system as an alternative medium of communication in Mat-y, Miag-ao, Iloilo. To determine acceptance, this study specifically intends to find out the respondents knowledge, attitude and practice towards the public address system as alternative media. This will also find out the other medium of communication that residents have access to in terms of local information Assessing the performance of the public address system or PA is something that has not been done in the past. By evaluating the people's acceptance towards this medium, this study can assess the PA system's performance as alternative media. This may serve as reference and baseline data for future studies using this similar medium. This study can also be beneficial to small and rural communities to acknowledge the possibility of using this medium as alternative media for their communities. This study uses descriptive research design. Purposive or judgmental sampling determined the selection of adult respondents from 77 households. Data gathering involves a household drop-off survey using questionnaires with yes-no questions for knowledge and practice categories, and the Likert scale for the attitude category. Responses were tabulated and analyzed through descriptive statistical tools using frequency counts and percentages. The researcher found out that the respondents have a high level of knowledge and favorable attitude towards the use of PA system as alternative media. However, they have a moderate level of practice towards announcements made through the PA system. After tabulating the answers from multiple choice questions, the researcher found out that residents of Barangay Mat-y preferred conversation as a means of communicating barangay-related information. Environmental noise coming from vehicles, animals and peple is the most common interference that hinders the PA system to be heard in the community.
Thesis (Undergraduate, Bachelor of Arts in Communication and Media Studies) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Public Address Systems